In Vitro and in Vivo Behavior of Liposomes Decorated with PEGs with Different Chemical Features - Mastrotto, Francesca; Brazzale, Chiara; Bellato, Federica; De Martin, Sara; Grange, Guillaume; Mahmoudzadeh, Mohamad; Magarkar, Aniket; Bunker, Alex; Salmaso, Stefano; Caliceti, Paolo (Molecular pharmaceutics, 2020)
The colloidal stability, in vitro toxicity, cell association, and in vivo pharmacokinetic behavior of liposomes decorated with monomethoxy-poly(ethylene glycol)-lipids (mPEG-lipids) with different chemical features were comparatively investigated. Structural differences of the mPEG-lipids used in the study included: (a) surface-anchoring moiety [1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE), cholesterol (Chol), and cholane (Chln)]; (b) mPEG molecular weight (2 kDa mPEG45 and 5 kDa mPEG114); and (c) mPEG shape (linear and branched PEG). In vitro results demonstrated that branched (mPEG114)2-DSPE confers the highest stealth properties to liposomes (∼31-fold lower cell association than naked liposomes) with respect to all PEGylating agents tested. However, the pharmacokinetic studies showed that the use of cholesterol as anchoring group yields PEGylated liposomes with longer permeance in the circulation and higher systemic bioavailability among the tested formulations. Liposomes decorated with mPEG114-Chol had 3.2- and ∼2.1-fold higher area under curve (AUC) than naked liposomes and branched (mPEG114)2-DSPE-coated liposomes, respectively, which reflects the high stability of this coating agent. By comparing the PEGylating agents with same size, namely, linear 5 kDa PEG derivatives, linear mPEG114-DSPE yielded coated liposomes with the best in vitro stealth performance. Nevertheless, the in vivo AUC of liposomes decorated with linear mPEG114-DSPE was lower than that obtained with liposomes decorated with linear mPEG114-Chol. Computational molecular dynamics modeling provided additional insights that complement the experimental results.
Keywords: Cholesterol; Drug Stability; Humans; HeLa buňky; povrchové vlastnosti; nanocarrier PEG coating; pharmacokinetic of liposomes; cholesterol; Drug Carriers; molekulová hmotnost; Liposomes; Phosphatidylethanolamines; fosfatidylethanolaminy; biologická dostupnost; lipidy; Cholanes; myši inbrední BALB C; lidé; zvířata; myši; Polyethylene Glycols; Mice; Biological Availability; simulace molekulární dynamiky; cholany; HeLa Cells; Molecular Dynamics Simulation; liposomy; Drug Compounding; nosiče léků; Lipids; příprava léků; stabilita léku; Animals; polyethylenglykoly; stealth liposomes; Surface Properties; Mice, Inbred BALB C; Molecular Weight